The Virtue ethics on charity of Benedict XVI and its correlation with the configuration to christ in ratio fundamentalis : a descriptive analytical approach - Corpuz, Jan Baeza L. (Mary Help of Christians Theology Seminary : [s.n.], 2020)
This thesp-study aims to help seminarians fowards Configuration to Christ so the h formation of theology seminary through the Virtue Ehies on Charity of Bedict XVI. The Ran Fundamentalis Instinations Sacerdotalis coins the term "Configuration to Chea of configuration stage for theology seminary formation St. John Paul Il emphasizes that the formation is the basis of all seminary formation Human formation refers to the intonal cultivation and formation of character of the whole human person to his natural perfection. The Philippines seminaries today are presently deepening and updating the programs of priestly formation in correlation with the latest document is seminary formation Ratio Fundamentalis Instinationis Sacerdotalis. The thesis-study is a participation of the researcher is the ongoing discussions on seminary formation particularly in the human formation of the theology seminary towards configuration to Christ, to be ipse Christus, Chrin himself. The Virtue Ethics verifies a person's character that is his identity, attitudes, and dispositions as the central elements in moral reasoning and action. The Virtue Ethics on charity of Benedict XVI defines love in the Greek terms of eros, agape, and philia. The novelty of the Virtue Ethics of Benedict XVI is the interrelation of eros and agape. The thesis-study endeavors for the deepening of the human formation of the configuration stage through the Virtue Ethics on charity of Benedict XVI. The charity namely cros, ajupe, and philia are subsistent towards configuration to Christ in the human formation. In essence, the correlation of Benedict XVI's chanty and RFIS configuration to Christ are harmonious God becomes neighbor of man and in Him, love for neighbor becomes love for God The eras of God is transformed to agape. The Virtue Ethics on charity of Benedict XVI, "the contemporary teacher of the Church," is prerequisite to explain the significance of love in responding to the theology seminary formation. This humble work endeavors its vision through the assistance of the Virtue Ethics of Benedict XVI.
Bibliography: pages 139-149.
CHED-La Union